Preliminary report on spiegelberg pre and post-operative monitoring of severe head-injured patients who received decompressive craniectomy - Abdullah Jafri, Jafri; Zamzuri, Idris; Awang, Mohamed Saufi; Sayuti , Sani; Ghani , Abdul Rahman; Tahir , Adnan; Naing, N.N (Springer-Verlag, 2005)
The monitoring of craniospinal compliance is uncommonly used clinically despite it’s value. The Spiegelberg compliance monitor calculates intracranial compliance (C ¼ DV/DP) from a moving average of small ICP perturbations (DP) resulting from a sequence of up to 200 pulses of added volume (DV ¼ 0.1 ml, total V ¼ 0.2 ml) made into a double lumen intraventricular balloon catheter. The objective of this study was thus to determine the e¤ectiveness of the decompressive craniectomy done on the worst brain site with regard to compliance (CI), pressure volume index (PVI), jugular oximetry (SjVo2), autoregulation abnormalties, brain tissue oxygen (TiO2) and cerebral blood flow (CBF). This is a prospective cohort study of 17 patients who were enrolled after consent and approval of the ethics committee between the beginning of the year 2001 and end of the year 2002. For pre and post assessment on compliance and PVI, all 12 patients who survived were reported to become normal after decompressive craniectomy. There is no significant association between pre and post craniectomy assessment in jugular oxymetry ( p > 0.05), autoregulation ( p > 0.05), intracranial brain oxymetry ( p ¼ 0.125) and cerebral blood flow ( p ¼ 0.375). Compliance and PVI improved dramatically in all alive patients who received decompressive craniectomy. Compliance and PVI monitoring may be crucial in improving the outcome of severe head injured patients after decompressive craniectomy